Checklist of lichenized and lichenicolous fungi from the Penyagolosa Massif and nearby areas (Castelló, eastern Iberian Peninsula) - Garrido-Benavent, Isaac; Escribano, Laura; Atienza, Violeta; Vidal, Lucía; Zamora, Juan Carlos; Chesa, María José; Force, Laura; Fos, Simón (Mediterranean Botany, 2024)
The Penyagolosa Massif (Castelló, Valencian Community), which includes the Penyagolosa Natural Park, is one of the most emblematic natural landscapes of the eastern Iberian Peninsula. It hosts a wide variety of Mediterranean habitats, including groves of several Quercus species and extensive Pinus spp. forests. The present checklist represents the first compilation of lichenized and lichenicolous fungi for the protected as well as nearby areas and is mostly based on species records available at the Biodiversity Data Bank of the Generalitat Valenciana (BDBCV). We report 221 and 12 infrageneric taxa of lichenized and lichenicolous fungi, respectively. Punctelia caseana is reported for the first time for the European continent. Six lichenicolous fungi are newly reported for the Valencian Community. The study area includes the red-listed lichen Xanthoparmelia camtschadalis. The families Parmeliaceae and Teloschistaceae showed the highest species richness. By evaluating the functional traits, we found that the most diverse lichens are those showing (1) crustose thalli, (2) with a sexual reproduction, mainly through the formation of apothecia, and (3) that are associated with trebouxioid green microalgae. Furthermore, the most frequent lichen community in the study area is formed by xerophytic lichens that can tolerate very high direct solar irradiation and develop under weak eutrophication conditions. Finally, we emphasize the need to accelerate the compilation of the diversity of lichenized and lichenicolous fungi in the park through DNA sequencing and molecular phylogenetics, which will also allow revealing the diversity of associated lichen photobionts and fungal-algal interaction patterns.